STRENGTHENING GOVERNANCE AND ECOSYSTEM CONSERVATION EDUCATION OF PUCUK KRUENG RIVER AS A FOUNDATION FOR SUSTAINABLE TOURISM DEVELOPMENT IN NAGA UMBANG VILLAGE: PENGUATAN TATA KELOLA DAN EDUKASI KONSERVASI EKOSISTEM SUNGAI PUCUK KRUENG SEBAGAI DASAR PENGEMBANGAN WISATA BERKELANJUTAN DI DESA NAGA UMBANG - Badruzzaman; Novi Mailidarni Novi; Rivai Ahmad; Jauhari; Juliawati; Tasliati Djafar (PT. ROCE WISDOM ACEH, 2026)
This community service program aimed to strengthen community governance capacity and enhance environmental awareness through ecosystem conservation education of the Pucuk Krueng River as a foundation for sustainable tourism development in Naga Umbang Village. The program employed a participatory approach involving socialisation, environmental education, group discussions, and conservation activities with village officials, community leaders, youth groups, and residents. The materials focused on river ecosystem conservation, waste management, and the role of local communities in supporting environmentally sustainable tourism. Evaluation was conducted through observation and participant discussions to assess changes in knowledge and engagement. The results showed an increase in community understanding of the ecological importance of the river and the need for conservation efforts to maintain environmental sustainability. Participants also demonstrated stronger commitment to preserving river cleanliness and supporting community-based tourism initiatives. Furthermore, the program fostered collaboration between local communities and village authorities in developing tourism strategies that integrate environmental, social, and economic sustainability. Continuous assistance and stakeholder collaboration are needed to ensure the long-term success of conservation-based tourism development in Naga Umbang Village